Reconstruction of the Regional Regulation Review Design Following the Constitutional Court Decision: Rekonstruksi Desain Pengujian Peraturan Daerah Pasca Putusan Mahkamah Konstitusi - Saifudin; Riza Hakiki, Yuniar; Retno Widiastuti; Taufiqurrahman; Wahyuningsih, Aprillia (Lex Renaissance, 2023)
This research aims to identify: first, the urgency of reconstructing the design of reviewing the regional regulations after the Constitutional Court decision, and second, reviewing the regional regulations which are in line with the system of regional government administration and the system of reviewing legislative regulations in Indonesia. This is a juridical-normative research. The results of the research conclude that: first, the urgency of reconstructing the review of regional regulations after the Constitutional Court decision is based on: a) the central government has lost control and correction of regional regulations; b) the problematic design of reviewing the regional regulations at the Supreme Court; and c) institutional problems of the Supreme Court in reviewing regional regulations. Second, the design of reviewing the regional regulations and the proposed regional legislation reviewing system, among others: a) expanding the clarification authority of the central government by canceling/revoking regional regulations whose content regulates the implementation of assistance tasks and/or regulates further elaboration of legal regulations -higher invitation by the central government/governor as a representative of the central government; and b) redesign of the Supreme Court's procedural law in reviewing statutory regulations by accommodating formal review; changing the concept of respondent to parties which include the applicant, the person providing information, and related parties; holding trials open to the public, forming a field (panel of judges) for reviewing statutory regulations; and extending the deadline for completing statutory examinations.Keywords: testing, regional regulations, Supreme Court, and Constitutional Court. AbstrakPenelitian ini bertujuan untuk mengetahui: pertama, urgensi rekonstruksi desain pengujian peraturan daerah pasca putusan Mahkamah Konstitusi, dan kedua, untuk mengetahui pengujian peraturan daerah yang sejalan dengan sistem penyelenggaraan pemerintahan daerah dan sistem pengujian peraturan perundang-undangan di Indonesia. Metode penelitian ini menggunakan yuridis-normatif. Hasil penelitian menyimpulkan: pertama, urgensi rekonstruksi pengujian peraturan daerah pasca putusan Mahkamah Konstitusi, didasari pada: a) pemerintah pusat telah kehilangan kontrol dan koreksi terhadap peraturan daerah; b) desain pengujian peraturan daerah yang problematik di Mahkamah Agung; dan c) problematika kelembagaan MA dalam pengujian peraturan daerah. Kedua, desain pengujian peraturan daerah dan sistem pengujian perundang-undangan daerah yang diusulkan, antara lain: a) memperluas kewenangan klarifikasi pada pemerintah pusat dengan melakukan pembatalan/pencabutan peraturan daerah yang materi muatannya mengatur pelaksanaan tugas pembantuan dan/atau mengatur penjabaran lebih lanjut peraturan perundang-undangan yang lebih tinggi oleh pemerintah pusat/gubernur sebagai wakil pemerintah pusat; dan b) redesain hukum acara MA dalam pengujian peraturan perundang-undangan dengan cara mengakomodasi pengujian formil; mengganti konsep termohon menjadi para pihak yang meliputi pemohon, pemberi keterangan, dan pihak terkait; melaksanakan sidang terbuka untuk umum, membentuk bidang (majelis hakim) pengujian peraturan perundang-undangan; dan memperpanjang batas waktu penyelesaian pemeriksaan pengujian perundang-undangan.Kata kunci: pengujian, peraturan daerah, Mahkamah Agung, dan Mahkamah Konstitusi.